Does Trade Drive Global Growth? - Leon Podkaminer (The Vienna Institute for International Economic Studies (wiiw), 2013)
Conventional econometric analysis using VEC suggests that there is a long-term relationship between nominal world GDP and nominal world exports. The analysis cannot say anything about the causal relationships between the levels of GDP and exports. But it says a lot about the rules governing the short-term adjustments in GDP and exports. When considering such short-term adjustments, GDP plays the first fiddle. Short-term GDP changes have driven short-term changes in world exports, at least over the years 1987-2008. But the short-term changes in world exports did not 'cause' positive short-term changes in GDP.
Keywords: F43; F15; O41; O49; 330; world income; world trade; growth; globalization; VEC; Granger causality